Inovasi kebijakan kepala daerah dari jalur perseorangan - Muhammad Ichsan Kabullah; Hendri Koeswara; Malse Yulivestra; Apriwan Apriwan; Nabilla Nabilla; Fathoni Nugrah Irkha (Komisi Pemberantasan Korupsi, 2023)
This article originates from the phenomenon of pairs of regional head candidates who advance and win through independent channels in regional elections. The presence of individual regional heads needs to be tested, especially when building a corruption-free government. The author takes the case of the recruitment of local government echelon officials, considering that this sector is very prone to corruption. The research was conducted in two areas where regional head positions were and are held by independent candidates, namely the City of Bukittinggi, West Sumatra Province and East Tanjung Jabung Regency, Jambi Province. The research method used is qualitative with data collection techniques in the form of in-depth interviews with many parties, literature studies, observation, and documentation. From the results of the research, it was found that the practice of buying and selling government positions that often occurs in many regions is actually not found in the two studied regions. Regional heads from these individual channels have succeeded in carrying out policy innovations by not intervening much and fully surrendering the mechanism for the recruitment process for echelon officials to the regulations. Even if changes are made, they are not prominent in nature and are always put forward under the principle of meritocracy. This in itself gives rise to stability in governance. For this reason, the existence of individual regional head candidates is shown to be linear with the corruption prevention agenda. Despite this, regional heads from individual channels still need strengthening, such as state funding support in Pilkada, affirmation of requirements, and more inclusive arrangements.